2020
DOI: 10.1002/advs.202000458
|View full text |Cite
|
Sign up to set email alerts
|

“Two Birds with One Stone” Ruthenium(II) Complex Probe for Biothiols Discrimination and Detection In Vitro and In Vivo

Abstract: In this work, a “two birds with one stone” ruthenium(II) complex probe, Ru‐NBD, is proposed as an effective tool for biothiols detection and discrimination in vitro and in vivo. Ru‐NBD is nonluminescent due to the quenching of Ru(II) complex emission by photoinduced electron transfer (PET) from Ru(II) center to NBD and the quenching of NBD emission through 4‐substitution with “O” ether bond. Ru‐NBD is capable of reacting with Cys/Hcy to form long‐lived red‐emitting Ru‐OH and short‐lived green‐emitting NBD‐NR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…In 2020, Liu et al reported a “Two Birds with One Stone” Ru(II) complex 54 for the detection and discrimination of biothiols in vitro and in vivo (Fig. 26 A) [ 224 ]. Complex 54 was developed through coupling of two different signaling units (Ru(II) complex and NBD) through a “luminophore-responsive linker-luminophore” approach.…”
Section: Ru(ii) Complex Chemosensors For Amino Acidsmentioning
confidence: 99%
“…In 2020, Liu et al reported a “Two Birds with One Stone” Ru(II) complex 54 for the detection and discrimination of biothiols in vitro and in vivo (Fig. 26 A) [ 224 ]. Complex 54 was developed through coupling of two different signaling units (Ru(II) complex and NBD) through a “luminophore-responsive linker-luminophore” approach.…”
Section: Ru(ii) Complex Chemosensors For Amino Acidsmentioning
confidence: 99%
“…To distinguish three different biothiols, Zhang et al designed and synthesized a bifunctional Ru(II) complex (Ru3), which could detect the total content of biothiols and discriminate GSH and Cys/Hcy simultaneously (Figure 13a). [53] The probe consisted of a longlived luminescent Ru(II) complex and a short-lived fluorescent 7-nitro-2,1,3-benzoxadiazoles (NBD) unit with an ether bond as a linker. The PET effect from Ru(II) complex to NBD quenched the long-lived luminescence of Ru(II) complex and the shortlived fluorescence of NBD simultaneously.…”
Section: Ru(ii) Complexes For Time-resolved Imaging Of Enzyme Activitymentioning
confidence: 99%
“…< Fig. 6 is here > Luminescent transition metal complexes have recently attracted enormous interests in the development of probes for biosensing and imaging due to their abundant photo-physical/-chemical properties and controllable cytotoxicity [47][48][49][50][51][52][53]. Among various metal complexes, luminescent platinum(II) (Pt(II)), ruthenium (II) (Ru(II)), rhenium(I) (Re(I)), and iridium(III) (Ir(III)) are contributing significantly to this field [54][55][56][57][58][59].…”
Section: Lipophilic Ligands As the Targeting Unitsmentioning
confidence: 99%